OPTIMIZED HORN DESIGN FOR RADIOMETER APPLICATION - Wihatmawati, Tryse; Christiyono, Yuli (Universitas Diponegoro, 2013)
Abstract A rectangular horn antenna is designed by March Microwave System B.V. and analyzed for its radiation pattern. The antenna is part of a radiometer which is used to measure the temperature inside baked food samples when they leave the oven. The horn antenna frequency was selected at 3.2 GHz, as a compromise between the shortest wavelength possible for optimal distance resolution and on the other hand the need for a long wave to achieve the desired depth of measurement. Calculations by CST Microwave Studio are done to simulate performance and to complete the analysis these are validated against the experimental results. The rectangular horn antenna is measured inside an anechoic chamber. Key: horn, radiometer, CST, anechoic chamber. Abstrak Antena Horn Persegi Panjang dirancang oleh March Microwave System B.V. dan dianalisa untuk pola radiasi. Antena merupakan bagian dari radiometer yang digunakan untuk mengukur suhu di dalam sampel makanan panggang ketika mereka melewati oven. Frekuensi antenna horn yang digunakan 3,2 GHz sebagai kompromi antara panjang gelombang sesingkat mungkin untuk resolusi jarak optimal dan disisi lain panjang gelombang dibutuhkan untuk mencapai kedalaman yang diinginkan dalam pengukuran. Perhitungan diselesaikanÂ oleh CST Microwave Studio untuk mensimulasi kinerja dan untuk melengkapi analisis tersebut divalidasi terhadap hasil percobaan. Antena Horn Persegi Panjang diukur dalam ruang anechoic. Â Kunci : horn, radiometer, CST, anechoic chamber.